De Novo Assembly and Comparative Analysis of the Enterococcus faecalis Genome (KACC 91532) from a Korean Neonate - Ham, J.S., RDA, Suwon, Republic of Korea; Kwak, W.R., Seoul National University, Seoul, Republic of Korea; Chang, O.K., RDA, Suwon, Republic of Korea; Han, G.S., RDA, Suwon, Republic of Korea; Jeong, S.G., RDA, Suwon, Republic of Korea; Seol, K.H., RDA, Suwon, Republic of Korea; Kim, H.W., RDA, Suwon, Republic of Korea; Kang, G.H., RDA, Suwon, Republic of Korea; Park, B.Y., RDA, Suwon, Republic of Korea; Lee, H.J., RDA, Suwon, Republic of Korea; Kim, J.G., RDA, Cheonan, Republic of korea; Kim, K.W., Seoul National University, Seoul, Republic of Korea; et al. (Journal of microbiology and biotechnology, 2013)
Using a newly constructed de novo assembly pipeline, finished genome level assembly had been conducted for the probiotic candidate strain E. faecalis KACC 91532 isolated from a stool samples of Korean neonates. Our gene prediction identified 3,061 genes in the assembled genome of the strain. Among these, nine genes were specific only for the E. faecalis KACC 91532, compared with all of the four known reference genomes (EF62, D32, V583, OG1RF). We identified genes related to phenotypic characters and detected E. faecalis KACC 91532-specific evolutionarily accelerated genes using dN/dS analysis. From these results, we found the potential risk of KACC 91532 as a useful probiotic strain and identified some candidate genetic variations that could affect the function of enzymes.